ASSESSMENT OF THE EFFECT OF THERAPEUTIC AND PREVENTIVE MEASURES ON THE ANTIMICROBIAL FACTOR OF THE ORAL CAVITY IN THE ORAL FLUID OF PATIENTS AFTER SURGICAL INTERVENTION TO REMOVE TUMORS AND CHEMOTHERAPY - Guliuk, S.A.; Shnaider, S.A.; Dienha, O.V.; Glazunov, O.A.; Skulska, S.V.; Diiev, Ye.V.; Honcharenko, O.V. (World of Medicine and Biology, 2025)
The study was devoted to the evaluation of the effect of a therapeutic complex of drugs on the indicator of the main antimicrobial factor of the oral cavity – lysozyme activity in the oral fluid of patients after surgical removal of tumors and chemotherapy. Thirty-five adults (25–55 years) were enrolled: a healthy control cohort, a comparison group receiving only standard oncologic care, and a main group receiving standard care plus the therapeutic and preventive complex. Non-stimulated whole saliva was collected at baseline and at 1-, 3-, 6-, and 12-month post-surgery. Lysozyme activity was quantified spectrophotometrically. Results were analysed with Student’s t-test (p